The enrichment of bladder cancer stem cells using three-dimensional (3D) spheroid culture system / Omar Nafiis Hairuddin - Hairuddin, Omar Nafiis (2024)
Bladder cancer is a malignancy with a very high rate of relapse. In addition, the presence of tumour-initiating cells also known as cancer stem cells are resistant to conventional treatment modalities. This study analysed methods to effectively enrich the CSCs population from two bladder cancer cell lines, 5637 and HT-1376 using two types of spheroid culture methods; multicellular spheroid (MCS) and single-cell derived spheroid (SCDS). Determination of spheroid formation potential, the expression of CSC surface markers (CD24/CD44, CD44/CD133, and CD133/CD24), pluripotent genes (SOX2, NANOG, and POU5F1), and differentiation potential were analysed in both spheroid cultures. Additionally, MCS and SCDS resistance towards cisplatin treatment and the expression of drug efflux gene (ABCG2) were determined by treating MCS and SCDS cultures with the IC50 dosage of cisplatin that was determined earlier in parental 5637 and HT-1376 and spheroid diameters were recorded. Results show that 5637 and HT-1376 could generate spheroids of various structures and cell-cell adhesion strength when subjected to MCS and SCDS culture methods. Spheroid diameters were significantly increased at day 10 post-culture compared to day 2 of MCS of 5637 (p<0.0001) and HT-1376 (p<0.001) and SCDS of 5637 (p<0.0001) and HT-1376 (p<0.0001). 5637 MCS produced higher population of CD133/CD24 (p<0.001) and CD24/CD44 (p<0.0001), while 5637 SCDS generated higher population of CD24/CD44 only (p<0.0001) when compared to parental cells. Meanwhile, HT-1376 MCS showed higher population of CD133/24 (p<0.001) and CD24/44 cells (p<0.0001), while HT-1376 SCDS showed higher population of cells expressing all the 3 surface markers combination, CD133/CD24 (p<0.001), CD24/CD44 (p<0.0001) and CD44/CD133 (p<0.0001) when compared to parental cells. 5637 SCDS expressed higher SOX2 (p<0.01), NANOG (p<0.0001), and POU5F1 (p<0.0001), while 5637 MCS expressed higher NANOG (p<0.001) and POU5F1 (p<0.001) only. Whereas both MCS and SCDS of HT-1376 demonstrated higher expression of all 3 pluripotent genes (p<0.0001) compared to parental cells. However, both cell lines showed no significant changes in differentiation potential following MCS and SCDS culture. HT-1376 exhibited higher IC50 compared to 5637 when subjected to treatment for 48 hours (2.61 µM and 1.15 µM, respectively) and 72 hours (7.00 µM and 4.20 µM, respectively). A significant increase in spheroid diameter of 5637 SCDS (p<0.001) and ABCG2 upregulation (p<0.0001) following cisplatin IC50 dosage treatment demonstrated that cisplatin resistance is associated with spheroid formation. However, HT-1376 SCDS showed no significant diameter change in parallel to ABCG2 downregulation when compared to parental (p<0.0001) and MCS (p<0.0001). In contrast, HT-1376 MCS exhibited significant diameter reduction before and after IC50 dosage treatment (p<0.05) although there was a significant ABCG2 upregulation when compared to parental cells (p<0.05) and SCDS (p<0.0001). However, there was no significant diameter change in 5637 MCS. To conclude, both the MCS and SCDS techniques significantly increased the population of bladder CSCs, however, the SCDS technique revealed a greater elevation of CSC markers and pluripotent gene expression. This study provides insight into the capability of spheroid culture to enrich the CSC population in bladder cancer cell lines. The MCS and SCDS culture methods can be used as models for CSC enrichment, cancer cell behaviour research, disease modelling, and personalised treatment research.